The effects of music tuition on academic achievement in portuguese 8th year students - dos Santos-Luiz, Carlos (2011)
The positive association between music lessons and academic achievement is well documented in the literature. Students who learn music show better academic achievements than those who are not involved in musical activities. However, this is a multifaceted association that can only be explained if several dimensions are taken into account, such as socioeconomic status (SES) or general intelligence (g). Significant differences in academic achievement were found between 8th year students who studied music (n=60) and those who did not (n=50) in five out of seven subjects analysed: natural sciences, physics and chemistry, Portuguese language, history, and geography. In addition, a multiple linear regression analysis was conducted in order to assess the role played by other potential dimensions (SES and general intelligence) in academic achievement. After including SES in the analysis, the results indicated that music tuition still contributed significantly to the given variance in academic achievement. However, in combination with all the factors (music tuition, SES, and general intelligence), music learning lost its statistical significance. Moreover, contrary to the majority of studies, one noteworthy finding was that SES had no significant impact on academic achievement. In conclusion, the results suggest that musical tuition does have a positive relationship to academic achievement.